EFEKTIVITAS METODE TUTOR SEBAYA DI MATA KULIAH STATISTIKA PADA MAHASISWA PSIKOLOGI - Tria Widyastuti; Rafli Sodiq Bagaskara; Ami Linta Zahrin (Universitas Muria Kudus, 2022)
The purpose of this research is to test the effectiveness of the peer tutoring method in improving statistics mastery.The research method used is a quasi-experimental method with a one-group pre and post-test design. The minimum sample size was determined based on the estimated number of samples using G*Power 3.1.9.7 software. Subject selection was carried out using a purposive sampling method with the criteria of Psychology students at UNY taking Statistics courses, while the number of samples was 35 students. This study involved two variables, namely the use of the peer tutoring method as the independent variable and mastery of statistics material as the dependent variable. After obtaining the data, data analysis was carried out by means of a paired sample t-test with JASP software version 0.13. Prior to testing, researchers conducted a normality test with Shapiro Wilk.The results of the study found that there was a significant increase in statistical scores on the post-test compared to the pre-test measurements after the peer tutoring method was applied for 2 meetings t (34) of -2.881 with a significance (p) of 0.007 and an effect size of Cohen's d 0.487. Thus, the peer tutoring method proved to be effective in increasing student mastery in Statistics courses.